PEMILIHAN BAHASA INDONESIA SEBAGAI BAHASA IBU PADA KELUARGA ETNIK MADURA DI KECAMATAN PATRANG - Anggraeni*, Astri Widyaruli (Belajar Bahasa, 2016)
This study examines the Indonesian choice language in Madura ethnic family as a mother tongue in District Patrang. Issues to be achieved is how social and psychological factors of parents in the realm of the family of the Indonesian language choice as a mother tongue in ethnic families of Madura in District Patrang. The collection of data in this research done twice: first, conducted to obtain information on family social background and the background of the language used in family communication which includes Madura language and Indonesian languages. Second, the data collection was done by purposive sampling, by using certain conditions. Analysis of the data used in this study is a qualitative correlation method. The study was based on social factor and psychological factors family, which is considered as a factor that causes and encourage Indonesian choice as the Indonesia language used in family communication.Key words: language choice, mother tongue, Madurese ethnic.